Challenges in the Diagnosis and Treatment of Aneurysmal Bone Cyst in Patients with Unusual Features - Ziyad M. Mohaidat; Salah R. Al-gharaibeh; Osama N. Aljararhih; Murad T. Nusairat; Ali A. Al-omari (Advances in Orthopedics)
Objectives. Aneurysmal bone cyst (ABC) is a benign but locally aggressive tumor. It has several challenging features. The aim of this study is to identify challenges in the diagnosis and treatment of ABC especially in patients with unusual features. Methods. This retrospective study involved medical record review of primary ABC patients with one or more of the following features: unusual clinical presentation with a mass or a pathological fracture especially at an unusual age, rare locations, radiological findings suggesting other diagnoses especially sarcoma, and a nondiagnostic histopathology of biopsy samples. Results. 25 patients (17 males and 8 females) were included. Most patients were either younger than 10 or older than 20 years. 10 patients presented with a mass or a pathological fracture. Unusual locations include the scapula, the olecranon, the hamate, the calcaneus, and the first metatarsal bone. Extension into the epiphysis occurred in 2 patients with proximal fibula and olecranon ABCs. Two separate synchronous cysts existed in the proximal epiphysis and middiaphysis of one humerus. Radiological imaging suggested other primary diagnoses in 8 patients. Core needle biopsy was diagnostic in only 2 of 7 patients. The main treatment was intralesional resection/curettage with bone grafting. Wide resection was performed in 4 patients. Recurrence rate was 28%. Recurrence risk factors included the following: age less than 10 years, male gender, and proximal femur location. Late recurrence occurred in 3/7 patients. One patient with asymptomatic radiological recurrence showed subsequent spontaneous resolution one year later. Conclusions. This study presented multiple unusual features of ABC including: unusual age, rare locations, and nondiagnostic radiological and histopathological findings. These features can complicate the diagnosis and management. Given these features, especially with pathological fractures, a well-planned incision, the use of frozen section examination, and the application of either external fixation or plate osteosynthesis for fracture fixation can be recommended.